Parcours et stratégies de professionnalisation militaire - Axel Augé (Temporalités)
The professionalization of the armed forces, incurred in 1996, transformed both the profession and the officer’s career. However, choosing to pursue an academic degree in a field marked by the operational reference is not easy. This is the reason why we are studying the social conditions for the academic professionalization and the individual strategies that the officers choose. This article focuses on army officers who graduate from universities. It aims to understand how personal investment in academic learning reinforces military professionalism and helps them shape their professional career. Two models of military professionalism, based on academic degrees, are highlighted. The first describes professional reconversion within the army; the second is based on a logic of identity quest, far from any institutional injunction. The analysis of professional trajectories based on graduate officers comes to moderate this categorization and provides an additional point of view on the social resources that officers gather in order to handle their military career.